Ductility of reinforced lightweight concrete beams and columns - Charif,Abdelhamid (2014)
This paper presents analytical and experimental results on ductility of reinforced lightweight concrete beams and columns in the form of moment curvature relationships, and compares the response with that of normal reinforced concrete members. The experimental part is limited to flexural tests on beams made of lightweight concrete. The latter is obtained with natural lightweight aggregates. Concrete and steel stress-strain models in compression and tension are integrated analytically through the section in order to derive the resulting moment and axial force. Lightweight concrete beams and columns showed a more ductile behavior than normal concrete members and the analytical model reproduced the response with very good accuracy. The lightweight ductility was more pronounced in columns subjected to axial compression forces and bending.